2015
DOI: 10.5194/acp-15-6087-2015
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical processing of aqueous atmospheric brown carbon

Abstract: Abstract. Atmospheric brown carbon (BrC) is a collective term for light absorbing organic compounds in the atmosphere. While the identification of BrC and its formation mechanisms is currently a central effort in the community, little is known about the atmospheric removal processes of aerosol BrC. As a result, we report on a series of laboratory studies of photochemical processing of BrC in the aqueous phase, by direct photolysis and OH oxidation. Solutions of ammonium sulfate mixed with glyoxal (GLYAS) or me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
308
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(339 citation statements)
references
References 84 publications
(130 reference statements)
31
308
0
Order By: Relevance
“…Most of these results are from laboratory experiments and require confirmation from field observations. Forrister et al (2015) use airborne observations of two fire events to show that the absorption associated with BrC decreases following emission, estimating a half-life for biomass burning BrC absorption of 9-15 h. However, this rate is much slower than that suggested by laboratory studies (5 min to 3 h) (Zhong and Jiang, 2011;Lee et al, 2014;Zhao et al, 2015), though none of these has explored how the absorption of primary BrC from biomass burning evolves under oxidizing conditions. Given the above uncertainties, field measurements of BrC are vital not only for constraining models but also for understanding the properties and transformations of this aerosol and its radiative impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these results are from laboratory experiments and require confirmation from field observations. Forrister et al (2015) use airborne observations of two fire events to show that the absorption associated with BrC decreases following emission, estimating a half-life for biomass burning BrC absorption of 9-15 h. However, this rate is much slower than that suggested by laboratory studies (5 min to 3 h) (Zhong and Jiang, 2011;Lee et al, 2014;Zhao et al, 2015), though none of these has explored how the absorption of primary BrC from biomass burning evolves under oxidizing conditions. Given the above uncertainties, field measurements of BrC are vital not only for constraining models but also for understanding the properties and transformations of this aerosol and its radiative impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their strong absorption in the near-ultraviolet and visible regions, nitrated phenols are classified as poorly characterized brown carbon (BrC) (Desyaterik et al, 2013;Teich et al, 2017). Though the absorption of BrC is weak compared to that of black carbon (BC), it can enhance the absorption of solar radiation and may have an indirect effect on regional climate (Feng et al, 2013;Mohr et al, 2013;Laskin et al, 2015;Lu et al, 2015;Zhao et al, 2015). Recent studies have shown that several semivolatile nitrated phenols, including nitrophenol, nitrocatechol, and methyl-nitrocatechol (NC), are important photochemical oxidation products of gas-phase precursors, which may play a part in the formation of secondary organic…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, light absorption properties of OA are influenced by intermolecular interactions resulting in formation of charge−transfer complexes between different OA molecules. 11,12 Numerous studies indicate that the optical properties of BrC evolve significantly as a result of various atmospheric processes such as oxidation, 13,14 solar irradiation, 15,16 changes in temperature 17 and relative humidity. 18−20 These factors make the chemical composition and concentration of BrC chromophores highly variable across sources and locations, 7,8 which in turn results in high uncertainties in predicting and mitigating their climate effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the optical properties of BrC may change as BBOA ages in the atmosphere, 29−31 whereas the effect of aging on light absorption strongly depends on the molecular structures of BrC. 15,16,32 It follows that structural characterization of BrC chromophores will facilitate understanding of their photochemical stability and chemical transformations necessary for the accurate prediction of radiative forcing by BrC. 3 The major challenge in the chemical characterization of BrC is distinguishing its light absorbing components (chromophores) from a majority of nonabsorbing aerosol constituents.…”
Section: ■ Introductionmentioning
confidence: 99%